2013
DOI: 10.1021/nl403874y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reversible Mg Insertion in Nanostructured Bi for Mg Ion Batteries

Abstract: Rechargeable magnesium batteries have attracted wide attention for energy storage. Currently, most studies focus on Mg metal as the anode, but this approach is still limited by the properties of the electrolyte and poor control of the Mg plating/stripping processes. This paper reports the synthesis and application of Bi nanotubes as a high-performance anode material for rechargeable Mg ion batteries. The nanostructured Bi anode delivers a high reversible specific capacity (350 mAh/gBi or 3430 mAh/cm(3)Bi), exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
203
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(212 citation statements)
references
References 61 publications
8
203
0
1
Order By: Relevance
“…These systems provide a relatively facile delivery of Mg 2+ ions in a chloride-free electrolyte and an 28,30,48,49 in cells with a working Mg electrode. However, these electrolytes suffer from low (≤87%) CE, significant overpotential, destructive incompatibilities with Mg metal resulting in passivation of the anode surface, and parasitic loss of electrolyte due to the electrochemical decomposition of solvent (e.g., AN) mimicking Mg-plating/insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These systems provide a relatively facile delivery of Mg 2+ ions in a chloride-free electrolyte and an 28,30,48,49 in cells with a working Mg electrode. However, these electrolytes suffer from low (≤87%) CE, significant overpotential, destructive incompatibilities with Mg metal resulting in passivation of the anode surface, and parasitic loss of electrolyte due to the electrochemical decomposition of solvent (e.g., AN) mimicking Mg-plating/insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 In addition, using 0.4 M Mg(TFSI) 2 in diglyme, ∼60 mAh/g was observed under repeated cycling in a cathode limited cell configuration. 16 Notably, repeated cycling of bismuth electrodes in non-corrosive lithium-free magnesium- * Electrochemical Society Active Member. Carbon nanotubes (CNT) have been reported to function effectively as current collecting electrode substrates, holding several advantages as electrode supports relative to metal foils.…”
mentioning
confidence: 98%
“…15 Liu and coworkers reported ∼300 mAh/g capacities for chemically synthesized bismuth nanotubes in special electrolyte consisting of a Mg(BH 4 ) 2 /LiBH 4 mixture. 16 In addition, using 0.4 M Mg(TFSI) 2 in diglyme, ∼60 mAh/g was observed under repeated cycling in a cathode limited cell configuration. 16 Notably, repeated cycling of bismuth electrodes in non-corrosive lithium-free magnesium- * Electrochemical Society Active Member.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas commercial microsphere Bi powder undergoes pulverization on cycling in a magnesium cell (Fig. 2), Shao et al 4 at the Pacific Northwest National Laboratory, Washington, demonstrated that bismuth nanotubes could be used in magnesium anodes with fast charge-discharge rates and a capacity of 303 mA h g -1 , even after 200 cycles. Very recently, Parent et al, also at the Pacific Northwest National Laboratory produced a Sb-Sn alloy that was electrochemically conditioned to form Sn-rich nanoparticles 5 ; scanning transmission electron microscopy indicated that these (<40nm) particles would have excellent performance in Mg battery anodes, although electrochemical data have not yet been reported.…”
Section: Magnesium Anodesmentioning
confidence: 99%